Ramaje sonoro : elogios de la marimba. - Obregón, Roberto; Villatoro, José Luis; Arango, Luis Alfredo; Aguilera, Julio Fausto; Morales Santos, Francisco (Guatemala : Cultura, 2018)
.
.
Edición conmemorativa de la Inauguración de la Escuela Nacional de la Marimba.
Keywords: .